Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1017/s0033291716001598
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal depression is associated with decreased placental expression of the imprinted gene PEG3

Abstract: BackgroundMaternal prenatal stress during pregnancy is associated with fetal growth restriction and adverse neurodevelopmental outcomes, which may be mediated by impaired placental function. Imprinted genes control fetal growth, placental development, adult behaviour (including maternal behaviour) and placental lactogen production. This study examined whether maternal prenatal depression was associated with aberrant placental expression of the imprinted genes paternally expressed gene 3 (PEG3), paternally expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 69 publications
2
50
1
Order By: Relevance
“…It has been shown to be important in nest building and nurturing behaviour in rodents (Champagne and Curley, 2009). We have recently shown in three independent cohorts that prenatal maternal depression is associated with a down regulation of placental PEG3 expression (Janssen et al, 2016). It is of interest in this regard that it has been found that women with high depressive symptom scores during mid pregnancy, but not when their infants were 8 months, had a 30% increased risk of low maternal responsiveness when the infant was 12 months compared to women with consistently low depression (Pearson et al, 2012b).…”
Section: Underlying Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to be important in nest building and nurturing behaviour in rodents (Champagne and Curley, 2009). We have recently shown in three independent cohorts that prenatal maternal depression is associated with a down regulation of placental PEG3 expression (Janssen et al, 2016). It is of interest in this regard that it has been found that women with high depressive symptom scores during mid pregnancy, but not when their infants were 8 months, had a 30% increased risk of low maternal responsiveness when the infant was 12 months compared to women with consistently low depression (Pearson et al, 2012b).…”
Section: Underlying Biologymentioning
confidence: 99%
“…The fetal genome regulates maternal physiology and behaviour via the placenta too (Broad and Keverne, 2011). The placenta produces hormones that act on the maternal hypothalamus, and can alter later mothering behaviour (Janssen et al 2016). The peptide PEG3 is of especial interest with regards to this.…”
Section: Underlying Biologymentioning
confidence: 99%
“…). Consistent with this hypothesis, recent data have identified a significant association between both symptoms of prenatal depression and clinically diagnosed depression with placental expression of both an imprinted gene and placental lactogen, a hormone predicted to be regulated by this gene . Determining the cause and effect relationships in human studies of pregnancy is challenging.…”
Section: Imprinted Genes Foetal Programming and Maternal Mood Disordersmentioning
confidence: 99%
“…Equally so, certain neurological changes in the mother must also occur in order to facilitate appropriate and proper care for her newborn [17]. In two recent studies, PL was linked to depression [22,23]. In the rst study [23], placenta samples from women with clinically diagnosed prenatal depression and as well as in those self-reporting signi cant symptoms of depression during pregnancy were found to have a signi cantly decreased level of PL ribonucleic acid (RNA) [23].…”
Section: Introductionmentioning
confidence: 99%
“…In two recent studies, PL was linked to depression [22,23]. In the rst study [23], placenta samples from women with clinically diagnosed prenatal depression and as well as in those self-reporting signi cant symptoms of depression during pregnancy were found to have a signi cantly decreased level of PL ribonucleic acid (RNA) [23]. In the second study [22], maternal serum PL taken just before birth was negatively associated with depression and anxiety scores assessed 10 weeks after birth.…”
Section: Introductionmentioning
confidence: 99%